The Development of Good Governance Administration Guidelines under Loei Local Administration Organization - Promkam, Khankaew; Noirid, Surachet (Journal for Developing the Social and Community, 2022)
The research aims to 1. Study the current situation. and desirable conditions and necessities of educational institution administration by using the principles of good governance for educational institutions Under the local government organization, Loei Province 2. Develop guidelines for school administration by using good governance. The research was divided into 2 phases. Phase 1 studied the current condition. and desirable conditions and necessities Of the 186 school administrators and teachers, according to the tables of Krazy and Morgan, the instrument was a questionnaire. The consensus index was 0.60 – 1.00, the discriminating power of the current condition questionnaire was 0.41-0.91 and the confidence value was 0.98, the desirable condition was 0.58-0.87 and the confidence value was 0.98. administering educational institutions using the principles of good governance for educational institutions by 8 academic subjects with knowledge of institutional governance from Focus Group Discussion. The results of the assessment of the appropriateness and feasibility of the guidelines were at a high level. The results of the research showed that 1) the current state of educational institution administration based on the principles of good governance Overall, it’s at a high level. The overall desirable condition was at a high level. Requirements need to develop guidelines. Sorted in descending order as follows: School administration using the rule of law, morality, value for money. principle of participation transparency principle and the principle of responsibility 2) The development guidelines are Educational administrators should search for knowledge about various information. in the regulations to be current Administrators should monitor teachers and personnel in their work. and spend the budget with honesty School administrators should arrange for teachers to go on a study tour in the field of technology for use in teaching and learning according to the situation. The administrators must involve all stakeholders in education, including teachers, students, parents and the community, to participate in educational management in school projects and activities throughout the year. Educational institutions should prepare an operational calendar in order to be in accordance with the operational plan. and executives distribute tasks in their responsibilities to personnel